Comparative In Vitro Immune Stimulation Analysis of Primary Human B Cells and B Cell Lines - Kristien Van Belle; Jean Herman; Louis Boon; Mark Waer; Ben Sprangers; Thierry Louat (Journal of Immunology Research)
B cell specific immunomodulatory drugs still remain an unmet medical need. Utilisation of validated simplified in vitro models would allow readily obtaining new insights in the complexity of B cell regulation. For this purpose we investigated which human B lymphocyte stimulation assays may be ideally suited to investigate new B lymphocyte immunosuppressants. Primary polyclonal human B cells underwent in vitro stimulation and their proliferation, production of immunoglobulins (Igs) and of cytokines, and expression of cell surface molecules were analysed using various stimuli. ODN2006, a toll-like receptor 9 (TLR9) agonist, was the most potent general B cell stimulus. Subsequently, we investigated on which human B cell lines ODN2006 evoked the broadest immunostimulatory effects. The Namalwa cell line proved to be the most responsive upon TLR9 stimulation and hence may serve as a relevant, homogeneous, and stable B cell model in an in vitro phenotypic assay for the discovery of new targets and inhibitors of the B cell activation processes. As for the read-out for such screening assay, it is proposed that the expression of activation and costimulatory surface markers reliably reflects B lymphocyte activation.